VECTOR AUTOREGRESSION: THE RELATIONSHIP BETWEEN MACRO AND MICROECONOMICS - AL Bara; Riyan Pradesyah (Proceeding International Seminar of Islamic Studies, 2023)
The research was conducted to see the relationship and influence of the rupiah exchange rate, non-performing financing, financing to deposits, and islamic bank profits. This study used time seris data, which was taken from the Financial Services Authority website. The method used in the study was Vector Auto Regression (VAR). The results of the research obtained are that there is a reciprocal relationship between  the Rupiah Exchange Rate, Non-Performing Financing, Financing To Deposits, and the profit of Islamic banks, this is seen from the results of the Granger Causality Test, where the F-statistical and Probability values are not equal to 0.  Meanwhile,  in the variance test, rupiah exchange rate decomposition affected the profit of Islamic banks by 1.65%, NPF affected net profit by 0.22%, and FDR affected the net profit of Islamic banks by 3.42%.